Genetic fabrication of functional silk mats with improved cell proliferation activity for medical applications. (19th September 2019) - Wang, Yuancheng; Xu, Sheng; Wang, Riyuan; Chen, Wenjing; Hou, Kai; Tian, Chi; Ji, Yanting; Yang, Qianqian; Yu, Ling; Lu, Zhisong; Zhao, Ping; Xia, Qingyou; et al.
Abstract : Functional silk mats with improved cell proliferation activity are promising medical materials to accelerate damaged wound healing and tissue repair. Abstract : Functional silk mats with improved cell proliferation activity are promising medical materials to accelerate damaged wound healing and tissue repair. In this study, novel functional silk mats were fabricated from human fibroblast growth factor (FGF)-containing cocoons generated by expressing human acid FGF1 and basic FGF2 in silkworms. First, functional silk mats containing FGF1 and FGF2 proteins alone or in combination were fabricated by physically cutting genetically engineered cocoons. Compared to those of normal silk mats, the physical properties of these functional silk mats such as silk fibre diameter, internal secondary structure, and mechanical properties were significantly changed. The expressed FGF1 and FGF2 proteins in these silk mats were efficiently and gradually released over 15 days. Moreover, these silk mats significantly promoted NIH/3T3 cell proliferation and growth by activating the extracellular signal-regulated kinase (ERK) pathway, and the silk mat containing FGF1 and FGF2 proteins showed higher cell proliferation. Importantly, this silk mat caused no obvious cytotoxicity or cell inflammation. These results suggest that these functional silk mats have potential medical applications.